2013
DOI: 10.1139/cjm-2012-0721
|View full text |Cite
|
Sign up to set email alerts
|

Identification of methicillin-resistant Staphylococcus aureus carrying an exfoliative toxin A gene encoding phage isolated from a hospitalized patient in Turkey

Abstract: From the four known isoforms of the staphylococcal exfoliative toxins (ETs), only ETA and ETB are the major causative agents. General knowledge is that the gene for ETA is located on the chromosome, whereas that for ETB is located on a large plasmid. Yoshizawa and co-workers (2000, Microbiol. Immunol. 44(3): 189-191) isolated, for the first time, a temperate phage (φETA) that carried the structural gene for ETA from an ETA-producing strain of Staphylococcus aureus. In this study, we presented eta gene encoding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Yamaguchi et al [32] also isolated a phage (φ ETA) that encodes an ETA from S. aureus, isolated from a human impetigo patient, and determined the complete nucleotide sequence of the φ ETA genome. Recently, we isolated an eta gene carrying phage obtained from MRSA strain isolated from the blood of the patient without any skin lesion [33]. Both in the previous study and this study, we showed that the MRSA φ ETA genome was different from the genomes of the other phages.…”
Section: Discussionmentioning
confidence: 50%
“…Yamaguchi et al [32] also isolated a phage (φ ETA) that encodes an ETA from S. aureus, isolated from a human impetigo patient, and determined the complete nucleotide sequence of the φ ETA genome. Recently, we isolated an eta gene carrying phage obtained from MRSA strain isolated from the blood of the patient without any skin lesion [33]. Both in the previous study and this study, we showed that the MRSA φ ETA genome was different from the genomes of the other phages.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, we observed significant transcriptional changes in S. aureus Newman_2010 upon exposure to the triple-acting fusion protein PGH1801 [ 2 , 12 ]. We found most of these are membrane proteins, cell wall related proteins [ 32 , 33 , 34 , 35 , 36 , 37 ], such as amidase [ 12 ], peptidase [ 29 ], holin [ 38 , 39 , 40 , 41 , 42 ], and phospholipase D/transphosphatidylase [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%